2011
DOI: 10.1002/rcm.4895
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of 13C and 15N isotope labeling by gas chromatography/combustion/isotope ratio mass spectrometry to study amino acid fluxes in a plant–microbe symbiotic association

Abstract: We have developed a method based on a double labeling with stable isotopes and gas chromatography/combustion/isotope ratio mass spectrometry (GC/C/IRMS) analyses to study amino acid exchange in a symbiotic plant–microbe association. Isotopic precision was studied for 21 standards including 15 amino acid derivatives, three N‐protected amino acid methyl esters, three amines and one international standard. High correlations were observed between the δ13C and δ15N values obtained by GC/C/IRMS and those obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 47 publications
1
30
0
1
Order By: Relevance
“…It should be noted that precision may vary considerably between labs, even for the same derivatization method and similar GC/C/IRMS protocols. For example, Molero et al . obtained average δ 15 N value precisions of 0.28‰ while Hofmann et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that precision may vary considerably between labs, even for the same derivatization method and similar GC/C/IRMS protocols. For example, Molero et al . obtained average δ 15 N value precisions of 0.28‰ while Hofmann et al .…”
Section: Resultsmentioning
confidence: 99%
“…The derivatization reactions and multiple purification steps of these procedures require hours for completion, and careful temperature control and anhydrous conditions are essential (Table ) . Derivatization via silylation is a simple, single‐step alternative, but silylated derivatives decrease oxidation reactor efficiency and may degrade capillary columns . Furthermore, silylation adds a large amount of non‐analyte carbon – at least six carbons per AA – which is expected to decrease the precision of δ 13 C measurements .…”
Section: Comparison Of the Reaction Times And Steps Required For Widementioning
confidence: 99%
“…So the identification of plant processes conditioning C sinks will be a key point in future plant breeding programs. The application of C and N stable isotopes to research in this area has been described previously (Avice et al, 1996b;Aranjuelo et al, 2008Aranjuelo et al, , 2009bMolero et al, 2011). Specifically, the application of 12 CO 2 labelling in a study conducted in slow growing plants (Aranjuelo et al, 2009b) revealed that the C sink/source imbalance was conditioned by plant growth, the leaf C residence time and a by the capacity to deliver recently fixed C to respiration.…”
Section: Utility Of C and N Isotopes In Climate Change Studiesmentioning
confidence: 97%
“…Organic acids provide reductant to both the Nase complex and the respiratory chain that fuels Nase with the ATP necessary for nitrogen fixation (Kouchi and Yoneyama , Streeter ). The bacteroid returns ammonium (NH 4 + ) to the host and this is assimilated in the form of amino acids that are partitioned to the rest of the plant through the xylem (Udvardi and Day , Molero et al ). Studies conducted in the past show that, after shoots are removed, nodule functioning is reduced during the first days of regrowth (Boucaud and Bigot , Ta et al ) and is concomitant with an 88% decrease in nitrogen fixation 24 h after cutting (Vance et al ).…”
Section: Introductionmentioning
confidence: 99%